Organoleptic Assessment of Tilapia (Oreochromis niloticus) Stored in Different Temperatures - M.N.M. Fouzi; Assanar Thaiuba; R.M. Nikzaad (PT FORMOSA CENDEKIA GLOBAL, 2023)
The current study was conducted to assess the freshness and pattern of spoiling of Nile tilapia (Oreochromis niloticus) stored at various temperatures. Nile tilapia purchased from NAQDA - Dambulla with same harvest and size; transported to the laboratory in ice boxes. Fish were randomly divided into four equal groups and stored in 4°C (n=6), -4°C (n=6), -10°C (n=6) & -20°C (n=6) temperatures. Basically, samples were evaluated for 41 days; daily for first five days & then once in two days for six days, once in three days for nine days & finally once in a week for 3 weeks. Organoleptic and demerit points were calculated. From the results, there were significant differences (p<0.05) in freshness of tilapia stored in four different temperatures. However, freshness deterioration in -10°C and -20°C were relatively slow but in 4°C it was rapid. In Sensory evaluation rejection was held at after 3 days (4°C), 14 days (-4°C), 27 days (-10°C) and 34 days (-20°C). Significantly positive correlation was observed between freshness deterioration and storage period r=0.99 (4°C), r=0.98 (-4°C), r=0.90 (-10°C) and r=0.92 (-20°C).